Expression of p53 in the Tumor and Oral Epithelium in Patients with Cancer of Mouth and Pharynx - Santos, Fabiane Dittrich; Montovani, Jair; Soares, Cleverson Teixeira; de Carvalho, Lídia Raquel (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: Expressive percent of patients with oral and oral pharynx carcinomas presents with overexpression of protein p53 induced by tobacco, alcohol and radiotherapy.Objective: To describe the p53 expression in areas of the normal mucosa adjacent to the tumor and in mouth and pharynx carcinomas.Method: Prospective study with clinical follow-up of one year of 24 patients with oral and oral pharynx spinocellular carcinoma. We performed biopsies in the neoplasm and areas of the normal mucosa adjacent to the tumor, before and 9 months following radiotherapy and an immunohistochemical study of p53 expression.Results: Before radiotherapy, there was a change to the p53 expression in 20 out of the 24 biopsies made in the neoplasm and in 14 in those of normal mucosa adjacent to the tumor. Eleven patients died 1 year before clinical follow-up. From the 2 initial patients with increase of p53 after radiotherapy it remained increased in 7 in the neoplasm region and in 6 in the normal mucosa regions. We noticed association of p53 with smoking and tumor stage (p < 5%), but not with the degree of cellular differentiation and alcoholism.Conclusion: The increase to the p53 expression was viewed both in the neoplasm region and in the normal mucosa in most patients with oral and oral pharynx carcinoma before and after radiotherapy. There was a statistically significant correlation of the p53 expression with smoking and neoplasm stage.
Keywords: mouth neoplasms; pharynx neoplasms; p53 genes; cocarcinogenesis